Model Probit Spasial pada Faktor-Faktor yang Mempengaruhi Klasifikasi IPM di Pulau Jawa - Puspita, Feni Ira; Ratnasari, Vita; Purhadi, Purhadi (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2013)
Human pembagunan Index (HDI) is a composite index that includes three basic dimensions of human development is considered to reflect the status of the population's basic abilities of health, educational attainment, and purchasing power. Data IPM classified into four, namely low, lower middle, upper middle, and high. Therefore, determining the HDI can be done with the data probit regression approach. In the data found that there were similarities between the HDI value of geographically adjacent regions which resulted in the classification of the adjacent HDI same region. This is presumably due to the inter-regional dependency. This phenomenon is suspected because of the spatial dependencies can be described through spatial methods. From the explanation above, the HDI of data in this study are based on the spatial probit regression method are compared with the probit method. This study aims to assess the predictors for estimating parameters and testing parameters were applied to the data classification IPM in Java. MCMC is used as a method of estimating the parameters in the assessment. While the assessment test parameters used are 25% to 75% of the estimated parameters